L-lactate reduces in vitro the inhibition of butyrylcholinesterase (bche) by paraoxon (e 600) - Petroianu, Georg; Kärcher, B.; Kern, N.; Hardt, F.; Helfrich, Ursula; Rüfer, Roderich (Journal of applied toxicology, 1999)
Intoxication with the organophosphorus compound paraoxon (POX), an inhibitor of serine hydrolases, is frequent. Oximes are the only enzyme reactivators clinically available. Serendipitous observation led us to the hypothesis that lactate might attenuate some of the POX effects. In vitro effects of lactate on the inhibition of butyrylcholinesterase (BChE) by POX were assessed in plasma of 12 healthy human volunteers. The determinations were repeated using different lactate and different POX concentrations. The BChE activity determinations were performed in the following settings:baseline untreated plasma (BL); ii after addition of POX to plasma (pl+POX); iii after POX and plasma were incubated and then lactate was added (pl+POX/lact); iv after addition of lactate to plasma (pl+lact); v after lactate and plasma were incubated and then POX was added (pl+lact/POX); vi after lactate and POX were incubated and then added to plasma (lact+POX/pl).In the micro- and millimolar ranges, lactate is able to abolish in vitro the inhibition of BChE by POX in human plasma when added to plasma prior to POX or when incubated with POX prior to addition to plasma. Lactate added to plasma after POX has no protective effect. In a second set of experiments, the effect of lactate on BChE activity was determined. At high millimolar concentrations, lactate itself inhibits BChE to an extent comparable to POX. Lactate is a mixed inhibitor of BChE, being able to interfere with the enzyme-substrate complex (inhibition constant for the enzyme-inhibitor-substrate complex K I (EIS)<<< WCODE [220] >>>rb<<< WCODE [220] >>>ee = 81 mM) and the enzyme (inhibition constant for the enzyme-inhibitor complex K I (EI) = 26 mM).
Gesehen am 30.05.2022